Analysis of the Understanding of State Administrative Law and Its Implications for the Quality of Public Services within the Brebes Regency Government - Faizal Yudhi Nugroho; Muamar Riza Pahlevi; Labib Fahmi; Fajar Sigit Kusumajaya; Dita Retno Pamungkas; Moh Syamsul Haris (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2026)
State Administrative Law (HAN) is an important instrument for regulating the implementation of clean and accountable governance. However, the level of understanding among State Civil Apparatus (ASN) regarding the principles of HAN often varies, potentially affecting public policy, bureaucratic performance, and the quality of public services. As observed in Brebes Regency, there remains a gap between senior ASN personnel with more than 20 years of service and ASN personnel who have held their positions for less than 5 years. To facilitate the transition toward an accountable digital bureaucracy, the Brebes Regency Government is advised to formulate a specific Brebes Regent Regulation (Perbup) concerning digital work procedures and data integration to provide legal certainty for technical implementing staff. Furthermore, HAN training programs/seminars should be organized for non-legal Regional Government Agencies (OPD), such as BKPSDMD, Kesbangpol, and subdistrict administrations, with a focus on digital administrative law, administrative discretion, and the mitigation of legal risks in public service delivery. The findings of this study are expected to provide a foundation for policymakers, particularly the Regent of Brebes, to strengthen the regulatory framework so that every public policy has a clear legal basis. Without a strong legal basis, public policies may result in administrative errors, potentially leading to lawsuits before the State Administrative Court (PTUN) or other legal proceedings.